THE EFFECT OF AEROBIC EXERCISE ON SOME BLOOD PARAMETERS OF PARTICIPANT WITH AUTISM - Yıldırım, Zeynep; Yıldırım, Zeynep (Int Journal Lifescience & Pharma Research, 2021)
This study aimed to determine the effect of aerobic exercise applied to participant with autism spectrum disorder (ASD) on some blood parameters. Based on this aim, a 13-year-old male with diagnosed autism spectrum disorder and who had not participated in any exercise program before was applied a total of 40 hours of the exercise program for 5 days a week for 8 weeks, and after this program, the effects of some blood parameters were investigated. The single-subject case analysis method, one of the scientific research techniques, was used in the study, and the pre-test and post-test modelling of the individual participating in the exercise program was performed. In the research, it was found that a positive relationship was observed between liver enzymes and exercise as ALT; Pre-test: 10.2 U/L Post-test: 20 U/L, AST; Pre-test: 28 U/L, Post-test: 33 U/L. Sodium; Pre-test: 120 mmol/L Post-test: 140 mmol/L Urea; Pre-test: 38 mg/dL, Post-test: 27 mg/dL, Uric Acid; Pre-test: 4.7 mg/dL, Post-test: 4.9 mg/dL in this reference range where toxin values were examined, it was determined that exercise had beneficial effects. Moreover, it was found that exercise had a positive effect mostly on thyroid hormone values as T3; Pre-test: 5.82 pg/mL Post-test: 4.99 pg/mL, T4; Pre-test: 13.96 pg/mL, Post-test: 10.82 pg/mL TSH; Pre-test: 5.01 mU/L Post-test: 4.8 mU/L. As a result, an eight-week aerobic exercise program applied to a participant with autism spectrum disorder and had a positive effect on the thyroid values of the participant.
Keywords: Autism; Blood Parameters; Aerobic Exercise